Involvement of nitric oxide in improving stress-induced behavioural alteration by glatiramer acetate treatment in female BALB/c mice - Pascuan, Cecilia Gabriela (2015)
Rationale: Oxidative stress and neurotrophins are among the most important factors involved in several pathophysiological brain processes. In addition, long-term exposure to stressful situations has deleterious effects on behaviour. We have previously shown that stressed female BALB/c mice show poor learning performance and that this behaviour is reversed by glatiramer acetate (GA) treatment. Objectives: We investigated the involvement of the hippocampal oxidative status and neurotrophin levels in cognitive deficit and the improvement of this deficit by GA treatment in chronic stressed BALB/c mice. Methods: Female BALB/c mice were exposed to a chronic mild stress (CMS) model for 9 weeks. During the last 3 weeks of the stress exposure, one group of mice was subcutaneously injected four times with 100 μg GA/mouse. Following this period, behavioural studies were performed. The mice were then sacrificed, and biochemical studies were performed on the hippocampus. Results: The stressed mice exhibited a significant decline in their performance in the open-field and in object-in-place tasks. This decline was accompanied by an increase in reactive oxygen species (ROS) and a decrease in nitric oxide (NO) production by neuronal nitric oxide synthase (nNOS). Neither antioxidant defences nor neurotrophin protein levels were involved in this process. Interestingly, the administration of GA re-established the normal levels of ROS, restored nNOS activity and improved learning performance. Conclusions: The GA treatment improved learning and memory in female BALB/c mice under chronic stress through a mechanism that involves the regulation of NO production, which in turn modulates the ROS levels.